The role of bars in triggering active galactic nucleus galaxies - Alvarez Vergara, Valeria Marels (2025)
Aims. Bars are considered an efficient mechanism for transporting gas toward the central regions of galaxies and potentially enhance nuclear activity. However, the extent to which bars influence active galactic nuclei (AGNs) and whether their efficiency varies with environment remain open questions. Methods. In this study, we aim to quantify the role of bars in triggering AGNs by comparing the AGN fraction in barred and non-barred galaxies across different environments. Results. We constructed a sample of barred and non-barred galaxies from the Galaxy Zoo DECaLS catalog, ensuring a control selection where the samples share similar distributions in stellar mass, redshift, magnitude, concentration index, and local density parameter. AGNs were identified using spectroscopic data from the Sloan Digital Sky Survey in order to obtain a final sample of barred AGN galaxies (1330) and a control sample of unbarred AGNs (1651). We employed the [OIII]λ5007 luminosity (Lum[OIII]) and the accretion rate parameter ℛ parameter as indicators of nuclear activity. Based on these parameters, we applied specific criteria to distinguish between powerful and weak AGNs, allowing for a more precise assessment of the potential impact of bars on the supermassive black hole. Conclusions. Our analysis reveals that barred galaxies tend to host a higher fraction of powerful AGNs compared to unbarred galaxies. From the analysis of Lum[OIII], we find that galaxies with higher values of nuclear activity tend to be massive, blue, and with young stellar populations. In addition, we observed a slight tendency for barred galaxies to host less massive black holes, which were found to accrete matter more efficiently. The classification analysis of strong and weak bars indicates that galaxies with a more prominent bars exhibit higher values of nuclear activity. Furthermore, we studied the environmental dependence of this trend. Although no significant differences between strong and weak bars were found in intermediate density environments, we observed a distinction in both low and high density environments, where galaxies with strong bars exhibit increased AGN activity.